(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يعالج هذا البحث المسألة القصوى الشرطية الآتية: أوجد القيمة الصغرى للدالي التكاملي تحت شروط إضافية من النوع حيث تابع معرف في فضاء باناخ للتوابع التحليلية في قرص الواحدة . لقد تم البرهان على أنه إذا كان حلاً للمسألة أعلاه فإنه يحقق المعادلات التفاضلية مع العلم أن متعلق بمضاريب لاغرانج. This paper deals with the following conditional external problem: find the minimum value of the integral functional under some boundary conditions and additional constraints where is some function defined in Banach Space of holomorphic functions in unit disc. It has been shown that the solution of the above problem satisfies the differential equations and is the Lagrange Multiplier.